Circadian variation of serum leptin and adipose tissue changes in children. Issue 2 (25th September 2022) - Zenno, Anna; Brady, Sheila M.; Faulkner, Loie M.; Ballenger, Kaitlin L.; Fatima, Syeda; Yanovski, Jack A.
Summary: Background: Higher morning serum leptin values are associated with larger adipose tissue gains in children; however, it is unclear if leptin circadian variation is itself associated with adipose tissue changes during growth. Objective: We studied the association of circadian variation in leptin with change in total body fat mass (TBFM), total body percentage fat (%FM), and trunk fat mass (TrFM). Methods: Baseline serum samples for leptin were obtained every 3 h for 24 h from 130 children (baseline age 9.6 ± 2.5y; 51.1% male; BMI‐Z 1.59) with mean follow‐up of 11.1 ± 4.0y and underwent dual‐energy x‐ray absorptiometry. ANCOVA models examined change in TBFM, %FM, or TrFM as dependent variables and number of years of follow‐up, sex, race, baseline age, pubertal status, initial visit body composition, and initial visit serum leptin circadian variables (maximal diurnal leptin [acrophase], diurnal amplitude, and percentage change of amplitude) as independent factors. Result: Although initial visit mesor (24 h average) leptin was positively associated with initial visit TBFM (r 2  = 0.78, p  < 0.001), %FM (r 2  = 076, p  < 0.001), and TrFM (r 2  = 0.71, p  < 0.001), none of the circadian leptin variables studied was significantly associated with change in TBFM, %FM, or TrFM. Conclusion: We found no evidence that circadian variation in serum leptin concentrations during childhood is associated with long‐term changes in children's adiposity.